When you are born matters: Evidence for England - Claire Crawford; Lorraine Dearden; Ellen Greaves (Institute for Fiscal Studies (IFS), 2013)
There is a long history of research in the UK and elsewhere showing that children who are born at the end of the academic year tend to have lower educational attainment than children born at the start of the academic year. In England, where the academic year runs from 1 September to 31 August, this means that children born in the summer tend to perform worse than children born in the autumn. There is also growing evidence that the month in which children are born matters for a range of other skills and behaviours as well, such as the likelihood of being assessed as having special educational needs at school, and children's self-esteem and confidence in their own ability. Why should this matter to policymakers? There are at least two reasons: first, because these differences in educational attainment and other skills and behaviours may affect children's well-being in the short term; and second, because they may have potentially serious long-term consequences for children's lives.
Keywords: 330